Genetic profiling of advanced radioactive iodine-resistant differentiated thyroid cancer and correlation with axitinib efficacy. Issue 2 (10th April 2015) - Schechter, Rebecca B.; Nagilla, Madhavi; Joseph, Loren; Reddy, Poluru; Khattri, Arun; Watson, Sydeaka; Locati, Laura D.; Licitra, Lisa; Greco, Angela; Pelosi, Giuseppe; Carcangiu, Maria Luisa; Lingen, Mark W.; et al.
Abstract Biomarkers predicting which patients with advanced radioiodine-resistant differentiated thyroid cancer (DTC) may benefit from multi-kinase inhibitors are unavailable. We aimed to describe molecular markers in DTC that correlate with clinical outcome to axitinib. Pretreatment thyroid cancer blocks from 18 patients treated with axitinib were collected and genomic DNA was isolated. The OncoCarta™ Mutation Panel was used to test for 238 oncogenic mutations. Copy number of VEGFR1-3 and PIK3CA was determined using qPCR on enriched tumor samples. Genomic DNA was analyzed for all coding regions of VEGFR1-3 with custom primers. Protein expressions of VEGFR1-3, c-Met, and PIK3CA were evaluated with immunohistochemistry. Clinical response to axitinib, including best response (BR) and progression free survival (PFS), was ascertained from corresponding patients. Fisher's exact test and logistic regression models were used to correlate BR with molecular findings. Cox proportional hazards regression was used to correlate PFS with molecular defects. A total of 22 pathology samples (10 primary, 12 metastatic) were identified. In patients with 2 samples (n = 4), genetic results were concordant and only included once for analysis. Tumors from 4 patients (22%) harbored BRAF V600E mutations, 2 (11%) had KRAS mutations (G12A, G13D) and 2 (11%) had HRAS mutations (Q61R, Q61K). One metastatic sample with mutated KRAS also harbored a PIK3CA (H1047R) mutation. qPCR showed increased copy numbers of PIK3CA in 6 (33%) tumors, VEGFR1 in 0 (0%) tumors, VEGFR2 in 4 (22%) tumors, and VEGFR3 in 6 (33%) tumors. VEGFR sequencing was significant for a possibly damaging non-synonymous SNP in VEGFR2 (G539R) in 2 samples (11%), a possibly damaging SNP in VEGFR3 (E350V) in 1 sample (6%), and a potentially novel mutation in VEGFR2 (T439I) in 2 samples (11%). Immunohistochemistry (VEGFR1, -2, -3; c-MET; PIK3CA) revealed positive staining in the majority of samples. No significant relationship was seen between BR or PFS and the presence of molecular alterations. Molecular evaluation of DTC specimens did not predict clinical response to axitinib but our data were limited by sample size. We did identify molecular changes in VEGFR that should be further explored. While DTC is genetically heterogeneous, primary and metastatic lesions showed identical oncogenic alterations in four cases.